Análise perturbativa em modelos cosmológicos fantasmas - Jardim, Deborah Faragó (2010)
Dark energy models have became extensively studied in recent years. Earlier proposals have emerged this century to describe the Universe by means of a fluid whose equation of state was breaking with the paradigm imposed by the standard cosmology. Fluid of this kind require to violate some energy conditions and have a very peculiar behavior, denominated for this reason "phantom fluid". This work investigates the structures formation through the study of cosmological perturbations in Universe which scenario is the phantom cosmology. They have proposed two models, the first them by solving the perturbed equations for scalar modes, using a hydrodynamic and fields representation for the fluid and then making the asymptotic behavior analysis. The second model is a composite of two fluids, one component of pressureless matter and another with negative pressure, represented by a self-interacting scalar field . In this case, the solution was obtained by numerical calculation. Results were confronted with the observational data and it showed models phantom of this nature are quite possible and its open a new window of research